Perception of Community Health Workers in Indonesia toward Patients with Mental Disorders - Shanti Wardaningsih; Takayuki Kageyama (Intelektual Pustaka Media Utama, 2016)
In Indonesia, there are any community health volunteers called Kader. Although Kaders are members of mental health volunteer, they sometimes show negative attitude to psychotic persons, even they have already got some training about mental health. The aims of this study were to investigate 1) how is Kader's perception compare to the other countries, 2) how will they consult compare to the other countries 3) how is comparison of Kaders’ perception to mental disorder person between trained and untrained. The method of this research is a descriptive explorative using survey study. This study was held on June to September 2013. It was conducted in five districts of Yogyakarta area with 619 respondents. The Questionnaires used contained three sections are follows; Part A is about Demographic Data, Part B two case vignettes (taken from MacArthur Health Module of the 1996 general Social Survey) and Part C about Kaders experiences. The perception of Kader as part of the community is lower than the general residence in the United States and Japan. The comparison between trained and untrained Kaders shown that trained Kaders has better perception toward patient with mental disorder. These results suggest that actual experiences in meeting the cases contributed to the improvement of Kaders’ perception better than the previous mental health training did. It might be Kaders with short experience are explored information Kaders should be trained with more structured curriculum and recruiting Kader is recommended to recruit the young generation.